Relative Motion Extension Splint after Extensor Tendon Reconstruction - Ayhan, Egemen; Arslan, Ozge Buket; Cevik, Kadir; Oksuz, Cigdem (Journal of Hand and Microsurgery, 2023)
Recently, the wide-awake local anesthesia no tourniquet (WALANT) technique and relative motion extension (RME) splint changed practice in extensor tendon reconstruction and therapy. We wanted to share our approach for zones 5 to 8 extensor tendon management following the up-to-date developments. The impacts of surgery under WALANT and early active motion therapy with RME splinting were explained frankly and shown in several videos throughout the article.
Keywords: WALANT; relative motion splint; yoke splint; extensor tendon; hand therapy